On the Uniqueness of Meromorphic Functions on Annuli in terms of Deficiencies. (28th January 2020) - Meng, Dawei; Lu, Nan; Liu, Sanyang
Abstract : The purpose of this article is to study the uniqueness of meromorphic functions on annuli. Under a certain condition about deficiencies, we prove some new uniqueness theorems of meromorphic functions on the annulus A = z : 1 / R 0 < z < R 0, where 1 < R 0 ≤ + ∞ .